Diffuse white matter lesions and cognitive functions - Kawamura, Mitsuru; Hasegawa, Yukihiro; Ichikawa, Hiroo; Fukui, Toshiya; Sugita, Koujiro (Japanese Journal of Stroke, 1997)
We investigated the cognitive functions and relevant factors in patients with diffuse white matter lesions. Out of 408 patients with asymptomatic cerebral infarction admitted during the period 1988-1996, we studied 15 patients who revealed diffuse white matter hyperintensities on T2-weighted magnetic resonance imaging. These patients were further divided into demented and nondemented subgroups on the basis of the results of the Hasegawa Dementia Scale Revised and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition (DSM-IV). All patients in the demented group also satisfied the diagnostic criteria of probable vascular dementia proposed by the National Institute of Neurological Disorders and Stroke-Association Internationale pour la Recherche et Enseignemant en Neurosciences (NINDS-AIREN). The control group consisted of 25 age-matched subjects with asymptomatic T2 hyperintensities. Patients in the nondemented and asymptomatic groups were also evaluated cognitively by the use of the “Kana-Hiroi” (Letter pick out) Test, Stroop test, Wisconsin Card Sorting Test, Raven Coloured Progressive Matrices and Kohs Block Design Test in addition to the Hasegawa Dementia Scale Revised. The demographic characteristics, amount and distribution of T2 hyperintensities larger than 3 mm on magnetic resonance imaging, thicknees of the corpus callosum, and ventricular indices were evaluated in the demented and nondemented patients. Subsequently, we addressed the following issues; 1) the differences in cognitive functions in the nondemented and control groups; 2) the factors relevant to cognitive functions in the nondemented patients; and 3) the lesion distributions in the demented and nondemented patients and factors discriminating these two groups. The results showed that : 1) the nondemented patients made more perseverative errors in the Wisconsin Card Sorting Test than did the control patients; 2) the amount of lesions in the frontal white matter and thalamus/posterior internal capsule, thickness of the corpus callosus, and educational level were related to cognition in the nondemented patients; and 3) the demenented patients had a significantly higher lesion distribution in the left thalamus/posterior internal capsule, which was the only factor significantly related to the presence of dementia. We concluded that cognitive function in the nondemented patients was characterized by more prominent frontal system dysfunction than in the control patients, and was influenced by multiple factors as well as the presence of white matter lesions. We also postulate that diffuse white matter lesions may predispose a patient to dementia by causing frontal system dysfunction, but not dementia per se unless additional lesions appear in the left thalamus which is closely associated with verbal memory.